Difference between revisions of "009B Sample Final 2, Problem 5"

From Grad Wiki
Jump to navigation Jump to search
 
(3 intermediate revisions by the same user not shown)
Line 3: Line 3:
 
::<math>y^3=x</math>
 
::<math>y^3=x</math>
  
<span class="exam">between <math style="vertical-align: -5px">(0,0)</math> and <math style="vertical-align: -5px">(1,1)</math> about the <math style="vertical-align: -4px">y</math>-axis.
+
<span class="exam">between &nbsp;<math style="vertical-align: -5px">(0,0)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">(1,1)</math>&nbsp; about the &nbsp;<math style="vertical-align: -4px">y</math>-axis.
  
 
<span class="exam">(b) Find the length of the arc  
 
<span class="exam">(b) Find the length of the arc  
Line 9: Line 9:
 
::<math>y=1+9x^{\frac{3}{2}}</math>
 
::<math>y=1+9x^{\frac{3}{2}}</math>
  
<span class="exam">between the points <math style="vertical-align: -5px">(1,10)</math> and <math style="vertical-align: -5px">(4,73).</math>
+
<span class="exam">between the points &nbsp;<math style="vertical-align: -5px">(1,10)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">(4,73).</math>
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
+
<hr>
!Foundations: &nbsp;
+
[[009B Sample Final 2, Problem 5 Solution|'''<u>Solution</u>''']]
|-
 
|'''1.''' The surface area &nbsp;<math style="vertical-align: 0px">S</math>&nbsp; of a function &nbsp;<math style="vertical-align: -5px">y=f(x)</math>&nbsp; rotated about the &nbsp;<math style="vertical-align: -4px">y</math>-axis is given by
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">S=\int 2\pi x\,ds,</math>&nbsp; where &nbsp;<math style="vertical-align: -19px">ds=\sqrt{1+\bigg(\frac{dx}{dy}\bigg)^2}dy.</math>
 
|-
 
|'''2.''' The formula for the length &nbsp;<math style="vertical-align: 0px">L</math>&nbsp; of a curve &nbsp;<math style="vertical-align: -5px">y=f(x)</math>&nbsp; where &nbsp;<math style="vertical-align: -3px">a\leq x \leq b</math>&nbsp; is
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp;<math>L=\int_a^b \sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math>
 
|}
 
  
  
'''Solution:'''
+
[[009B Sample Final 2, Problem 5 Detailed Solution|'''<u>Detailed Solution</u>''']]
  
'''(a)'''
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|We start by calculating &nbsp;<math style="vertical-align: -16px">\frac{dx}{dy}.</math>
 
|-
 
|Since &nbsp;<math style="vertical-align: -17px">x=y^3,~ \frac{dx}{dy}=3y^2.</math>
 
|-
 
|Now, we are going to integrate with respect to &nbsp;<math style="vertical-align: -3px">y.</math>
 
|-
 
|Using the formula given in the Foundations section,
 
|-
 
|we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{S} & = & \displaystyle{\int_0^1 2\pi x \sqrt{1+(3y^2)^2}~dy}\\
 
&&\\
 
& = & \displaystyle{2\pi \int_0^1 y^3 \sqrt{1+9y^4}~dy.}
 
\end{array}</math>
 
|-
 
|where &nbsp;<math style="vertical-align: 0px">S</math>&nbsp; is the surface area.
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.
 
|-
 
|Let &nbsp;<math style="vertical-align: -5px">u=1+9y^4.</math>
 
|-
 
|Then, &nbsp;<math style="vertical-align: -5px">du=36y^3dy</math>&nbsp; and &nbsp;<math style="vertical-align: -14px">\frac{du}{36}=y^3dy.</math>
 
|-
 
|Also, since this is a definite integral, we need to change the bounds of integration.
 
|-
 
|We have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>u_1=1+9(0)^4=1</math>&nbsp; and &nbsp;<math>u_2=1+9(1)^4=10.</math>
 
|-
 
|Thus, we get
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{S} & = & \displaystyle{\frac{2\pi}{36} \int_1^{10} \sqrt{u}~du}\\
 
&&\\
 
& = & \displaystyle{\frac{\pi}{27} u^{\frac{3}{2}}\bigg|_1^{10}}\\
 
&&\\
 
& = & \displaystyle{\frac{\pi}{27} (10)^{\frac{3}{2}}-\frac{\pi}{27}.}
 
\end{array}</math>
 
|}
 
 
'''(b)'''
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we calculate &nbsp;<math style="vertical-align: -15px">\frac{dy}{dx}.</math>
 
|-
 
|Since &nbsp;<math style="vertical-align: -5px">y=1+9x^{\frac{3}{2}},</math>&nbsp; we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{dy}{dx}=\frac{27\sqrt{x}}{2}.</math>
 
|-
 
|Then, the arc length &nbsp;<math style="vertical-align: 0px">L</math>&nbsp; of the curve is given by
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>L=\int_1^4 \sqrt{1+\bigg(\frac{27\sqrt{x}}{2}\bigg)^2}~dx.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Then, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>L=\int_1^4 \sqrt{1+\frac{27^2x}{2^2}}~dx.</math>
 
|-
 
|Now, we use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.
 
|-
 
|Let &nbsp;<math style="vertical-align: -14px">u=1+\frac{27^2x}{2^2}.</math>
 
|-
 
|Then, &nbsp;<math style="vertical-align: -14px">du=\frac{27^2}{2^2}dx</math>&nbsp; and &nbsp;<math style="vertical-align: -14px">dx=\frac{2^2}{27^2}du.</math>
 
|-
 
|Also, since this is a definite integral, we need to change the bounds of integration.
 
|-
 
|We have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>u_1=1+\frac{27^2(1)}{2^2}=1+\frac{27^2}{2^2}</math> and &nbsp;<math>u_2=1+\frac{27^2(4)}{2^2}=1+27^2.</math>
 
|-
 
|Hence, we now have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>L=\int_{1+\frac{27^2}{2^2}}^{1+27^2} \frac{2^2}{27^2}u^{\frac{1}{2}}~du.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
|-
 
|Therefore, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{L} & = & \displaystyle{\frac{2^2}{27^2} \bigg(\frac{2}{3}u^{\frac{3}{2}}\bigg)\bigg|_{1+\frac{27^2}{2^2}}^{1+27^2}}\\
 
&&\\
 
& = & \displaystyle{\frac{2^3}{3^4} u^{\frac{3}{2}}\bigg|_{1+\frac{27^2}{2^2}}^{1+27^2}}\\
 
&&\\
 
& = & \displaystyle{\frac{2^3}{3^4} (1+27^2)^{\frac{3}{2}}-\frac{2^3}{3^4} \bigg(1+\frac{27^2}{2^2}\bigg)^{\frac{3}{2}}.}
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp;'''(a)'''&nbsp; &nbsp; <math>\frac{\pi}{27} (10)^{\frac{3}{2}}-\frac{\pi}{27}</math>
 
|-
 
|&nbsp; &nbsp;'''(b)'''&nbsp; &nbsp; <math>\frac{2^3}{3^4} (1+27^2)^{\frac{3}{2}}-\frac{2^3}{3^4} \bigg(1+\frac{27^2}{2^2}\bigg)^{\frac{3}{2}}</math>
 
|}
 
 
[[009B_Sample_Final_2|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Final_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:28, 2 December 2017

(a) Find the area of the surface obtained by rotating the arc of the curve

between    and    about the  -axis.

(b) Find the length of the arc

between the points    and  


Solution


Detailed Solution


Return to Sample Exam